Key Factors Related to Stunting in Indonesia - Oktorina, Sarita (International Conference on Sustainable Health Promotion, 2018)
Stunting prevalence in Indonesia each year has increased prevalence. Stunting is one of the chronic malnutrition problems caused by a lack of nutritional intake for a long time due to food insecurity that is not in accordance with the required nutritional adequacy. Stunting occurs from the fetus and will appear when the child is two years old. Nutritional deficiencies that have occurred in early childhood can cause frequent illnesses, and can even cause infant and child death. If the child is often affected by the disease, it can interfere with the process of metabolism of nutrients in the body which will cause the child to have a posture that is not optimal in adulthood. There are many factors that cause children to be stunted, among them are diet, parenting and environmental sanitation. The purpose of this study is to find out how diet, parenting, and environmental sanitation can affect stunting in children. The method used is literacy studies. The results of this study are the existence of diet, parenting and environmental sanitation can affect the incidence of stunting in children.